en el Espacio Fugado. - Maso, Alfonso; Espacio Fugado Granada (Granada : Diputación de Granada, 2000)
Beltran, Marta ; Cabrera, Evaristo ; Calleja, Javier ; Castillo, Ruth ; Ceballos, Miguel M. ; Sanchez Valle, Ernesto ; Escobedo Ruiz, Alberto ; Delgado, Jacobo ; Garcia, Estefania ; Garcia Cruz, Manuel ; Garcia Roldan, Angel ; Giraldez, Ruth ; Gonzalez, Reyes ; Jimenez, Yolanda ; Leon, Laura ; Jimenez, Oscar ; Lopez Rodriguez, Silvia ; Belen Mañas, Ana ; Medina, Ana ; Melgares, Miguel Angel ; Moreno, Cristina ; Orozco, Aridane ; Perez, Silvia ; Peron, Carmen ; Polo, Beatriz ; Ruiz, Isabel ; Piñero, J. Antonio S. ; Serrano, Juan ; Weber, Charlotte
Spaans
BB.AA. promocion 2000 en el Espacio Fugado. Espacio Fugado Granada, Diputación de Granada, 06.07 - 03.09.2000
boek